PF.36 Audit of Congenital Central Nervous System (CNS) Anomalies: Patterns of Referrals and Service Implications After the Introduction of First Trimester Screening and Second Trimester Anomaly Ultrasound in South East Scotland. (26th April 2013) - Russell, H; Moore, E; Bayman, E; Cooper, S; Tallur, K; Murdoch, E
Abstract : 67 cases of fetal CNS anomalies from January 2010 – December 2011 were retrospectively reviewed. 80.6% from within the tertiary unit, and 19.4% referred from district general hospitals. Further investigations included chromosomal diagnosis; 1 CVS (normal), 7 amniocentesis (5 abnormal), 7 declined. Serology showed 3 positive for cytomegalovirus IgM. Fetal MRI was performed in 19 cases (28.4%) at average gestation 25+3. A second MRI in 2 cases (2.9%) at average gestation of 31+6. MRI was declined in 4 cases (5.9%). MRI confirmed the diagnosis or added additional information in 84.2%. Pregnancy outcomes were 23 livebirths, 43 terminations (5 fetocide) and 2 neonatal deaths. Post-mortem was performed in 55.2% of cases (86.1% of terminations). The findings added information in 40% of cases, including 4 further chromosomal abnormalities. Of the livebirths, 43.4% of babies were admitted to the Neonatal ICU with an average hospital admission of 21 days. Postnatal USS was performed in 82.6% and MRI in 52.2%. 82.6% had outpatient follow-up: 21.7% had a normal outcome, 21.7% showed global or isolated motor delay, and 13.1% were deceased. All were too early for a formal Baileys 2 year outcome. The management of congenital CNS anomalies requires significant multidisciplinary care, sequential USS and often additional MRI. This audit had added information which can inform the care pathway.